Pembelajaran Immersive Berbasis Metaverse dan Penguatan Kesehatan Mental di SMA Negeri 1 Manggis: Metaverse-Based Immersive Learning and Mental Health Enhancement at SMA Negeri 1 Manggis - Ketut Agustini; Luh Nik Armini; I Ketut Andika Pradnyana; I Nengah Eka Mertayasa; I Gede Bendesa Subawa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
The community service program at SMA Negeri 1 Manggis focused on improving the quality of learning through immersive learning technology based on the metaverse and strengthening the management of students’ mental health. The background of this program was the low ability of teachers in utilizing innovative learning media and the high prevalence of psychological issues among students, with data showing that 30% experienced stress, 10% anxiety, and 5% depression. The program was implemented using the mentorship learning method involving 47 teachers. The activities included socialization, immersive technology training, the formulation of a Standard Operating Procedure (SOP) for Student Mental Health Management, the “Care for Mental Health, Care for the Future” campaign, the use of VR Meta Quest devices, and the utilization of the Spatial.io platform. Evaluation was carried out through pre-tests, post-tests, and observation. The results showed that 75% of teachers understood immersive learning technology and 90% were able to produce interactive teaching modules. In terms of management, 80% of teachers were able to detect early signs of psychological problems, along with a 15% reduction in high absenteeism rates. The campaign also increased student participation in self-care activities by up to 70% and enhanced their comfort in consulting with guidance and counseling teachers by 85%.